How to Make 8, 1, 2‐closo‐MC2B9 Metallacarboranes1. Issue 45 (26th September 2014) - Man, Wing Y.; Zlatogorsky, Sergey; Tricas, Hugo; Ellis, David; Rosair, Georgina M.; Welch, Alan J.
Abstract Three examples of the rare 8, 1, 2‐closo‐MC2B9 isomeric form of an icosahedral metallacarborane have been isolated as unexpected trace products in reactions. Seeking to understand how these were formed we considered both the nature of the reactions that were being undertaken and the nature of the coproducts. This led us to propose a mechanism for the formation of the 8, 1, 2‐closo‐MC2B9 species. The mechanism was then tested, leading to the first deliberate synthesis of an example of this isomer. Thus, deboronation of 4‐(η‐C5H5)‐4, 1, 8‐closo‐CoC2B10H12 selectively removes the B5 vertex to yield the dianion [nido‐(η‐C5H5)CoC2B9H11]2−, oxidative closure of which affords 8‐(η‐C5H5)‐8, 1, 2‐closo‐CoC2B9H11 in moderate yield.